Healthy Relationships on the Autism Spectrum (HEARTS): A feasibility test of an online class co-designed and co-taught with autistic people. (April 2022) - Rothman, Emily F; Graham Holmes, Laura; Caplan, Reid; Chiang, Melody; Haberer, Brandy; Gallop, Nick; Kadel, Rabindra; Person, Mariah; Sanchez, Amelia; Quinn, Emily; Wharmby, Peter
This study tested the feasibility and preliminary efficacy of a six-session online class on healthy relationships for autistic individuals ages 18–44 years old ( N  = 55). The content of the Healthy Relationships on the Autism Spectrum class was informed by formative research with 25 autistic individuals, and developed collaboratively by two non-autistic professionals and seven autistic self-advocates. Fifty-five autistic people participated in Healthy Relationships on the Autism Spectrum and completed pre- and post-surveys. The study found that it was feasible to deliver Healthy Relationships on the Autism Spectrum online. Pairing an autistic and non-autistic person to co-teach was well-received. Participants decreased hostile automatic thoughts ( p  < 0.05), involvement in dating abuse in intimate relationships ( p  < 0.05), fight-or-flight response ( p  < 0.05), and rejection sensitivity ( p  < 0.001). Participants experienced improved flourishing ( p  < 0.001), coping with rejection and jealousy ( p  < 0.001), motivation to engage with others for socializing ( p  < 0.05), self-compassion ( p  < 0.05), and positive thinking ( p  < 0.05). Scores on a measure of interpersonal competence did not change, and loneliness did not decrease. The majority of participants reported high satisfaction with the class. Healthy Relationships on the Autism Spectrum is a promising healthy relationships promotion class that should be evaluated through a randomized controlled trial. Lay abstract: The Healthy Relationships on the Autism Spectrum class is unique because autistic people helped to develop it and co-taught it. It is an online, six-session class. The class was piloted in 2020–2021 with 55 autistic people who were ages 18–44 years old. This feasibility study found that most people who took the class liked it. Surveys filled out by the students before and after the class showed that they became less sensitive to rejection, used more positive thinking skills, and were more interested in being social. However, the class may not have made them feel less lonely. The team that invented the class is using the feedback to improve it. The class holds promise for improving the quality of friendships and dating relationships for autistic adults and should be tested further.